Cord blood leptin is associated with size at birth and predicts infancy weight gain in humans. ALSPAC Study Team. Avon Longitudinal Study of Pregnancy and Childhood. - Ong, K; Ahmed, M; Sherriff, A; Woods, K; Watts, A; Golding, J; Dunger, D (1999)
Recent discoveries of human genetic leptin deficiency have demonstrated its importance in regulating weight gain in early childhood. To investigate whether normal variation in leptin and insulin levels in cord blood could influence infancy growth, we assayed samples from 197 infants from a representative birth cohort, who were measured at birth, 4, 8, 12 and 24 months. Cord leptin levels correlated most closely with weight and ponderal index (kg/m3) at birth, but also with length and head circumference (all p<0.0005). Independent of birth size, females had higher leptin levels than males (p<0.0005). Cord levels of leptin, but not insulin, were negatively related to weight gain (p<0.005) from birth to 4 months, and accounted for 9.4% of the variance in weight gain, compared with breast/bottle feeding (3.5%) and early/late introduction of solids (1%). The effect of leptin levels on weight gain was independent of birthweight, and was still evident at 24 months. The wide variation in infancy growth ('catch-up' or 'catch-down') may be partly determined by leptin levels preset in utero. Our data support a role for leptin in the regulation of infancy weight gain, and suggest a mechanism whereby infants may 'catch-up' in growth postnatally following an adverse intrauterine environment.